Selected aspects of patient health in nuclear medicine - Wróbel, Grzegorz Paweł (Journal of Education, Health and Sport, 2017)
Nuclear radiation plays an important role in nuclear medicine. The health risk to patients undergoing screening only concerns the fact of gamma-ray emission, of course, the magnitude of this risk is dose-dependent. The purpose of the study is to assess patient safety in ionizing radiation studies in the light of applicable laws. The principle of optimizing the health protection of people subjected examinations using ionizing radiation mainly concerns the choice of the best protection option under specific exposure conditions and the greater benefits of ionizing radiation to the potential damage that could be caused by radiation exposure. Unfortunately, in some cases, patients are unnecessarily exposed to ionizing radiation during the diagnostic process, often as a result of lack of supervision of doses or undue imaging studies by physicians. Due to the numerous evidence highlighting the negative impact of high doses of ionizing radiation on the human body, we are not able to accurately track and evaluate all mechanisms of its action.